Popular music and the construction of noms de guerre in Zimbabwe's Guerrilla war - Pfukwa, Charles (Routledge, 2021)
Guerrilla movements in the Third World often espouse anti-Western ideologies. Many Zimbabwean guerrillas in the Zimbabwean liberation war (1966–79) took up noms de guerre that expressed this. However, a number of them took up names from cultural forms that represented the very enemy that they were fighting against; such as the names drawn from motion pictures, popular music and pop art of the time. This is one of the greatest ironies of a conflict where the guerrillas were trying to redefine themselves politically, socially and culturally, and yet they took the names of their adversaries. This paper explores some of these war names that were drawn from western cultural forms and religion. The paper will argue that the nickname as an onomastic category often is a subtle expression of the social, cultural and political environment of the bearer.